Functional evaluation of rare variants in complement factor I using a minigene assay - Donelson, Cobey J. H.; Ghiringhelli Borsa, Nicolo; Taylor, Amanda O.; Smith, Richard J. H.; Zhang, Yuzhou (Frontiers in Immunology, 2024)
The regulatory serine protease, complement factor I (FI), in conjunction with one of its cofactors (FH, C4BP, MCP, or CR1), plays an essential role in controlling complement activity through inactivation of C3b and C4b. The functional impact by missense variants in the CFI gene, particularly those with minor allele frequencies of 0.01% to 0.1%, is infrequently studied. As such, these variants are typically classified as variants of uncertain significance (VUS) when they are identified by clinical testing. Herein, we utilized a minigene splicing assay to assess the functional impact of 36 ultra-rare variants of CFI. These variants were selected based on their minor allele frequencies (MAF) and their association with low-normal FI levels. Four variants lead to aberrant splicing–one 5’ consensus splice site (NM_000204.5: c.1429G>C, p.Asp477His) and three exonic changes (c.355G>A, p.Gly119Arg; c.472G>A, p.Gly158Arg; and c.950G>A, p.Arg317Gln)–enabling their reclassification to likely pathogenic (LP) or pathogenic (P) based on ACMG guidelines. These findings underscore the value of functional assays, such as the minigene assay, in assessing the clinical relevance of rare variants in CFI.